The Fourth Mini-Symposium of Young Scientists ‘Stem Cell Day’, November 8, 2017 - Problems of Cryobiology; Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1):094–095